Research on extractive distillation of binary heterogeneous mixtures - V. M. Raeva; A. Yu. Sebyakin (Тонкие химические технологии)
Processes of heterogeneous extractive distillation and extractive distillation with heterogeneous binary mixtures were considered. Entrainers were chosen according to the thermodynamic criterion. The variation of pressure can be used for targeted changes in the relative volatility of the separated components in ternary systems.